Shareholders and Stakeholders around the World: The Role of Values, Culture, and Law in Directors' Decisions - Amir N. Licht; Renee B. Adams (Goethe University, Center for Advanced Studies on the Foundations of Law and Finance (LawFin), 2020)
We present evidence on the way personal and institutional factors could together guide public company directors in decision-making concerning shareholders and stakeholders. In a sample comprising more than nine hundred directors originating from over fifty countries and serving in firms from twenty three countries, we confirm that directors around the world hold a principled, quasi-ideological stance towards shareholders and stakeholders, called shareholderism, on which they vary in line with their personal values. We theorize and find that in addition to personal values, directors' shareholderism level associates with cultural norms that are conducive to entrepreneurship. Among legal factors, only creditor protection exhibits a negative correlation with shareholderism, while general legal origin and proxies for shareholder and employee protection are unrelated to it.
urn:nbn:de:hebis:30:3-616537
Keywords: K22; M14; 330; shareholderism; stakeholders; directors; values; culture; social norms; law; institutions; corporate governance; CSR; ESG; entrepreneurship